PENGARUH KOMPETENSI PEDAGOGIK DAN MOTIVASI GURU RUMPUN PAI TERHADAP PRESTASI BELAJAR SISWA DALAM RUMPUN MATA PELAJARAN PAI DI MTS AL-AZHAR PAGARALAM - sulismanto sulismanto (IAIN Bengkulu, 2017)
Abstract: Subyek research,testing hypothetkal done using stratifled random sampling technique by using a questionnaire to obtain data x1,x2 and y the data taken from the the value of the ist half-year student report cards 2014-2015 lessons. As for the techiniques used in data collction are using the questionnaires,observation,intervlen and documentation.Research data were collected and analyzed using product moment correlation analysis and analysis of the double regesi hypothesis, testing reseanah is conducted showed no effea of pedagoalcal competence and motivation of Islamic rellgious education teachers secra together on learning achievement student problem was evidenced by the results of the calculation stastisik on taraf significanded of 1% indicate that r count larger than r table is: 058470.413 The of its significance was tested using the F test and obtained Fn of 9575, F table = 4.10 become aritmeticf table, Which means significance regression equation so that the variable pedagogic and motivation of Islamic religious education teachers have a posive and significance effect on the variable student achievement in clumps lesson eye study Islamic religion in mts al-Azhar pagaralam.